Role of wild birds in the circulation of Toxoplasma gondii in Southern Italy: molecular and epidemiological insights - Serra, Francesco; Scarcelli, Stefano; Sgroi, Giovanni; Riccardi, Marita Georgia; Badri, Milad; Paone, Marco; Rea, Simona; Levante, Martina; Di Lecce, Emanuela; Borriello, Giorgia; Cecere, Bianca; D'Alessio, Nicola; et al. (Frontiers in Veterinary Science, 2026)
IntroductionToxoplasmosis is caused by the protozoal parasite Toxoplasma gondii and can be acquired through the consumption of food and water contaminated with sporulated oocysts and tissue cysts. The parasite is characterized by high host flexibility, being able to infect all warm-blooded animals, including birds and mammals. Wild birds are considered important reservoirs of infectious agents, some of which possess zoonotic potential. To date, few data are available on the role of these animals in the transmission of T. gondii, especially in the Italian Peninsula.MethodsTo address this gap, the present study investigated the circulation and genetic diversity of this parasite in various wild bird species, with the aim to assess the role of avian hosts in the epidemiology of the parasite. In 2023–2024, 256 carcasses belonging to 39 different wild bird species were collected in Campania and Calabria Regions and analyzed to assess the presence of T. gondii in the animal tissues.ResultsOut of 256 birds, 15 (5.9%) resulted positive for parasite DNA: 6 (40.0%) belonged to genotype GII and 1 (6.6%) to genotype GIII. Interestingly, 11/15 (73.3%) infected animals were non-migratory species and 10/15 (66.7%) were classified as omnivore/scavenger wild birds.DiscussionMonitoring and genotyping T. gondii in birds could help to understand the environmental spread of oocysts. What's more, given the remarkable ecological diversity of wild avian species (different feeding habits and migratory behavior), surveillance of avian populations could deepen our understanding of T. gondii transmission dynamics and implement public health interventions and environmental management strategies.